Clinical and genetic associations for carboplatin‐related ototoxicity in children treated for retinoblastoma: A retrospective noncomparative single‐institute experience. Issue 5 (19th January 2018) - Soliman, Sameh E.; D'Silva, Crystal N.; Dimaras, Helen; Dzneladze, Irakli; Chan, Helen; Gallie, Brenda L.
Abstract: Background: Children with retinoblastoma treated with carboplatin chemotherapy risk moderate to severe, irreversible hearing loss. Based on published evidence, we hypothesized that ototoxicity risk is associated with clinical parameters and variants in candidate genes in drug metabolism pathways (methyltransferases [thiopurine S‐methyltransferase, TPMT ] and [catechol‐O‐methyltransferase, COMT ], and drug transporter ABCC3 ). Procedure: We retrospectively reviewed clinical records of patients with retinoblastoma treated with carboplatin chemotherapy regarding age (at diagnosis and chemotherapy initiation), chemotherapy sessions (cycles number, drug doses, and cumulative carboplatin dose), and hearing loss (defined as ototoxicity ≥grade 2 by at least one classification system). Blood samples were genotyped for genetic variants in TPMT (rs12201199, rs1800460), COMT (rs4646316, rs9332377), and ABCC3 (rs1051640) by quantitative PCR and confirmed by allele‐specific PCR. Univariate statistical tests, receiver‐operating characteristic analysis, and Kaplan–Meier curves were used to examine the association between hearing loss, clinical factors, and variants in candidate genes. Results: Audiometric data and stored DNA were available for 71 patients with retinoblastoma (88% carried an RB1 pathogenic variant allele). Median carboplatin cumulative dose was 1, 400 mg/m 2 (260–5, 148 mg/m 2 ). Ototoxicity occurred in 18 patients (25%), strongly associated with age at diagnosis ( P  = 0.01) and age at chemotherapy initiation (OR = 4.99, P  = 0.008). The highest likelihood ratio of hearing loss was associated with chemotherapy initiation <4.25 months of age. Ototoxicity was not associated with any tested genetic variants. Conclusions: We observed a 25% prevalence of ototoxicity in patients with retinoblastoma treated with carboplatin, higher than previously published. Age at chemotherapy initiation was associated with carboplatin‐induced ototoxicity, with children <4.25 months of age at highest risk.